Sistem Inventory Koperasi Berbasis Website Di Koperasi SMP Pgri 2 Ciledug - Reyyan, Keimal; Alfiansyah, Sahrul; Farhan, Sandi; Haryono, Wasis (Jurnal Ilmu Komputer dan Teknologi Informasi, 2025)
This study aims to design and implement a website-based cooperative inventory system at SMP PGRI 2 Ciledug to improve the efficiency and accuracy of managing goods and transaction data. The previous inventory data management system still relied on Microsoft Excel, which is prone to human error, data duplication, and makes it difficult to track the history of incoming and outgoing goods. In addition, there is no automatic stock notification feature, manual reporting, and no sharing of user access rights, which hinders transparency and accountability. The implementation results show that this system is able to record stock in real-time with automatic updates, provide notification features when stock is running low, and automate the creation of transaction and profit reports. The user-friendly interface and integrated data backup feature also ensure ease of use and data security. Thus, this website-based inventory system significantly improves transparency, operational efficiency, and accountability of inventory management at the SMP PGRI 2 Ciledug cooperative, and supports a faster and more accurate decision-making process.